Interaction between liquid droplets and membrane surfaces; Separation and Purification Technology; Vol. 354, pt. 7 - Islamova A. G. Anastasiya Gomilievna; Shulyaev S. A. Stanislav Antonovich; Shlegel N. E. Nikita Evgenjevich; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen.